High-thermal-conductivity ceramic material and additive manufacturing method thereof
By combining modified aluminum nitride powder with photocured prepolymer and monomer, photocuring technology is used to print and cure layer by layer, solving the problem of poor thermal conductivity of aluminum nitride ceramics in the prior art, and achieving high thermal conductivity and high precision ceramic material preparation.
Patent Information
- Application Number
- CN202411972104.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art is difficult to take into account both high curing depth and curing accuracy, resulting in poor thermal conductivity of the prepared aluminum nitride ceramics.
Modified aluminum nitride powder is prepared by ball milling and mixing aluminum nitride, sintering aid, wetting dispersant and organic solvents, and vacuum ball milling is mixed with photocured prepolymer and monomer to prepare photocured ceramic slurry, and layer by layer printing and curing is used using photocuring technology, and finally obtain highly thermally conductive ceramic material through cracking, degreasing and sintering.
The high interlayer bonding strength, high solid content and high body accuracy of the aluminum nitride ceramic body are achieved, and the thermal conductivity after sintering is higher than 200W/m·K, which significantly improves the thermal conductivity of the ceramic.
Smart Images

Figure CN119661234A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum nitride ceramics, and in particular to a high thermal conductivity ceramic material and an additive manufacturing method thereof. Background Art
[0002] Aluminum nitride (AlN) ceramics have the characteristics of high thermal conductivity, excellent dielectric properties, low thermal expansion coefficient and good insulation performance. They are widely used in high-power integrated circuits, electrical devices, optics and intelligent manufacturing with high heat dissipation requirements. In order to maximize the heat dissipation capacity of aluminum nitride ceramic components, aluminum nitride ceramic components can be designed as heat sink structures with complex shapes or microchannels. Traditional forming methods such as dry pressing and isostatic pressing are suitable for preparing aluminum nitride ceramic materials with simple shapes, and tape casting is only suitable for preparing AlN substrates with a thickness of less than 1mm. For parts with complex shapes, mechanical processing methods are used. Due to the high hardness and brittleness of aluminum nitride ceramics, machining has the problems of high cost and high loss; gel injection molding and hot injection molding require the use of molds, resulting in long processing cycles and increased costs, which limits the development and application of aluminum nitride high thermal conductivity ceramics. Additive manufacturing (3D printing) uses the layering-superposition principle to slice and layer the three-dimensional model constructed by computer modeling software into continuously superimposed two-dimensional models, and then manufacture and superimpose them layer by layer to obtain a three-dimensional entity. 3D printing has the advantages of high flexibility and no need for molds. It can realize the free molding of parts and is widely used in complex structural ceramics. Additive manufacturing technologies mainly include binder jetting (BJ), direct writing (DIW), layered object manufacturing (LOM), fused deposition modeling (FDM), selective laser melting (SLM), stereolithography (SLA) and surface exposure molding (DLP). Among them, SLA and DLP both belong to photopolymerization (VPP), which is to mix ceramic powder with photosensitive resin liquid, and prepare complex-shaped devices through light induction and layered photopolymerization. It has great application potential in the additive manufacturing of functional ceramics.
[0003] High solid content and low viscosity ceramic slurry is the primary problem in photocuring 3D printing ceramic molding. High solid content is beneficial to increase the density of the green body and the ceramic body, reduce sintering shrinkage and reduce crack formation; low viscosity helps to evenly coat the slurry during printing to obtain a complete ceramic green body. In addition, in 3D printing, the layers must have good bonding strength to avoid the occurrence of green body delamination, warping and other phenomena. This requires the ceramic slurry to have a high single-layer curing thickness and optimize the layering thickness. Due to the high refractive index and absorbance of aluminum nitride, it is difficult for ultraviolet light to penetrate aluminum nitride slurry, resulting in a low single-layer curing thickness. Although increasing the ultraviolet light power and exposure time can increase the single-layer curing depth to a certain extent, it is accompanied by an increase in over-curing width and reduced molding accuracy. In order to solve the problem of low curing depth of aluminum nitride, researchers used powder coating technology to deposit Y(NO3)3 on the surface of AlN powder, and formed yttrium aluminate (YAG) on the surface of aluminum nitride powder by low-temperature (450°C) calcination and high-temperature (1500°C) nitrogen atmosphere treatment, reducing the absorbance of aluminum nitride powder to 405nm ultraviolet light to 0.171, thereby improving the curing depth of the slurry (Additive Manufacturing 74 (2023) 103732). This method requires pretreatment and calcination of aluminum nitride powder, which has cumbersome steps and complex processes, and the types of aluminum nitride sintering aids are limited to yttrium oxide. Patent CN 117776734 A discloses an aluminum nitride ceramic part and a forming method thereof, which improves the curing depth of the slurry by grading aluminum nitride powders of three different particle sizes. Nano-scale aluminum nitride powder in graded powder has a high specific surface area and activity, and is easy to absorb oxygen or water in the air, resulting in an increase in oxygen content. The thermal conductivity of AlN ceramics is closely related to the oxygen content, because oxygen will replace nitrogen to form aluminum vacancy defects, increasing phonon scattering; the thermal conductivity of the second phase formed by the oxide layer formed on the surface of aluminum nitride powder reacting with the sintering aid during the sintering process is much lower than that of aluminum nitride materials, thereby deteriorating the thermal conductivity of aluminum nitride ceramics. Powders with larger particle sizes can increase the curing depth, but at the same time also increase the curing width, resulting in reduced precision.
[0004] Therefore, there is an urgent need to provide an additive manufacturing method for high thermal conductivity ceramics using aluminum nitride to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a high thermal conductivity ceramic material and an additive manufacturing method thereof, so as to solve the technical problems in the prior art that it is difficult to achieve both high curing depth and curing accuracy when preparing aluminum nitride ceramics using photopolymerization technology, and the thermal conductivity of the prepared aluminum nitride ceramics is poor.
[0006] In a first aspect, the present invention provides a method for additive manufacturing of a high thermal conductivity ceramic material, comprising the following steps: The aluminum nitride, the sintering aid, the first wetting and dispersing agent and the organic solvent are ball-milled and mixed, and then dried and sieved to obtain modified aluminum nitride powder; Mixing the photocurable prepolymer and the photocurable monomer by vacuum ball milling to obtain a photocurable premixed liquid; Under light-proof conditions, the modified aluminum nitride powder, the photocuring premix, the second wetting and dispersing agent, the plasticizer and the photoinitiator are vacuum ball-milled to obtain a photocuring ceramic slurry; According to the three-dimensional model of the component, light-cured ceramic slurry is used to print and cure layer by layer to obtain an aluminum nitride ceramic body; The aluminum nitride ceramic body is cracked, degreased and sintered in sequence to obtain a high thermal conductivity ceramic material.
[0007] In a second aspect, the present invention provides a high thermal conductivity ceramic material, which is obtained by the additive manufacturing method of the high thermal conductivity ceramic material provided by the first aspect of the present invention.
[0008] Compared with the prior art, the beneficial effects of the present invention include: The aluminum nitride ceramic green body prepared by the present invention has strong interlayer bonding, high solid content, high green body precision (overcuring width is less than 100 μm), and thermal conductivity after sintering is higher than 200 W / m·K. The method of the present invention has simple process steps. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 The ultraviolet absorbance spectrum of aluminum nitride powder, a wetting and dispersing agent, and the modified aluminum nitride powder obtained in step (1) of Example 1 of the present invention; Figure 2 is a cross-sectional SEM image of the aluminum nitride ceramic body obtained in step (4) of Example 1 of the present invention; Figure 3 is an optical photograph of the high thermal conductivity ceramic material obtained in step (5) of Example 1 of the present invention; Figure 4 This is a SEM image of the aluminum nitride ceramic material obtained in step (5) of Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0011] In a first aspect, the present invention provides a method for additive manufacturing of a high thermal conductivity ceramic material, comprising the following steps: S1. Modification of aluminum nitride: Aluminum nitride, a sintering aid, a first wetting and dispersing agent, and an organic solvent are ball-milled and mixed, and then dried and sieved to obtain modified aluminum nitride powder; S2, preparing a photocurable premixed liquid: mixing a photocurable prepolymer and a photocurable monomer by vacuum ball milling to obtain a photocurable premixed liquid; S3, preparing a photocurable ceramic slurry: in a light-proof condition, vacuum ball-milling the modified aluminum nitride powder, the photocurable premixed liquid, the second wetting and dispersing agent, the plasticizer and the photoinitiator to obtain a photocurable ceramic slurry; S4, 3D printing: according to the three-dimensional model of the component, light-cured ceramic slurry is used to print and cure layer by layer to obtain an aluminum nitride ceramic body; S5. Cracking, degreasing and sintering: The aluminum nitride ceramic body is first cracked in a protective atmosphere, then degreased in air, and finally sintered in a nitrogen atmosphere to obtain a high thermal conductivity ceramic material.
[0012] The present invention adjusts the refractive index difference between the aluminum nitride powder and the resin by adding rare earth fluorides and oxides with low absorbance and can also be used as sintering aids to the aluminum nitride powder, thereby reducing the absorbance of the powder and improving the curing depth; the present invention adopts a phosphate wetting and dispersing agent, which can not only achieve good dispersion of the AlN powder and mutual solubility with the photosensitive resin, thereby reducing the viscosity of the slurry, but also has a higher refractive index, which can improve the comprehensive performance of the slurry. The addition method is divided into two steps. One part is adsorbed on the surface of the powder during ball milling of the ceramic powder, and relies on the electrostatic steric hindrance to promote the uniform dispersion of ceramic powders of different densities and reduce the absorbance of the powder to improve the curing depth; the other part is used to achieve effective wetting and dispersion of the solid powder in the resin when preparing the photocurable ceramic slurry, thereby reducing the viscosity of the photocurable slurry. The present invention can improve the printing molding accuracy by adding a plasticizer to the photocurable ceramic slurry, and solves the problem that microcracks are easily generated during degreasing of the blank. The present invention can evenly crack the photocurable resin by first cracking the aluminum nitride ceramic body in a protective atmosphere, reduce the generation of a large amount of gas, and avoid direct thermal oxidation decomposition in the air, which causes defects such as cracking of the ceramic due to the excessively fast decomposition rate of the photosensitive resin; then degreasing in the air can reduce the carbon residue produced by thermal cracking, and avoid direct cracking in a protective atmosphere to cause a large amount of carbon residue to hinder the subsequent densification sintering of the ceramic; finally, sintering is performed in a nitrogen atmosphere to prevent the oxidation of aluminum nitride and ensure the stability of the chemical composition. The aluminum nitride ceramic body prepared by the present invention has strong interlayer bonding, high solid content, high body precision (overcuring width is less than 100μm), and the thermal conductivity after sintering is higher than 200W / m·K. The method of the present invention has simple process steps.
[0013] In this embodiment, in step S1, the aluminum nitride is micron-sized aluminum nitride, and its average particle size is 1-2 μm.
[0014] In this embodiment, in step S1, the sintering aid is a combination of at least one of samarium fluoride and samarium oxide and yttrium fluoride, and the added amount thereof is 5% to 7% of the mass of aluminum nitride.
[0015] Preferably, yttrium fluoride accounts for 25% to 60% of the total mass of the sintering aid.
[0016] In this embodiment, in step S1, the average particle size of the sintering aid is 1-2 μm.
[0017] In this embodiment, in step S1, the first wetting and dispersing agent is a phosphate wetting and dispersing agent, and the amount of the first wetting and dispersing agent added is 0.5% to 1% of the total mass of the aluminum nitride and the sintering aid.
[0018] In some specific embodiments of the present invention, the first wetting and dispersing agent is BYK110.
[0019] In this embodiment, in step S1, the organic solvent is ethanol, and the amount of ethanol added is 70% to 80% of the total mass of the aluminum nitride and the sintering aid.
[0020] In this embodiment, in step S1, the ball milling method is planetary ball milling, the ball milling time is 5-10 hours, the ball milling speed is 300-400 rpm, the ball milling medium is zirconia balls with a diameter of 2-10 mm, and the mass ratio of zirconia balls to aluminum nitride is (3-5):1.
[0021] In this embodiment, in step S1, the mesh size of the sieve is 100-200 meshes.
[0022] In this embodiment, in step S2, the photocurable prepolymer is a difunctional aliphatic polyurethane acrylate with low viscosity (about 350 mPa·s). The present invention uses a difunctional aliphatic polyurethane acrylate with low viscosity as a photocurable prepolymer, which can effectively reduce the viscosity of the photosensitive resin, make the cured single layer have good toughness and strength, reduce the generation of multi-layer stress, and avoid bending and deformation of the blank.
[0023] In this embodiment, in step S2, the photocurable monomer is a combination of o-phenylphenoxyethyl acrylate (OPPEA), 1,6-hexanediol diacrylate (HDDA) and ethoxylated pentaerythritol tetraacrylate (PPTTA). The present invention can increase the refractive index of the photosensitive resin by introducing a monofunctional monomer with a high refractive index of 1.576, thereby increasing the curing depth; the present invention can increase the reaction activity, reduce the viscosity, and reduce the volume shrinkage by introducing a difunctional monomer 1,6-hexanediol diacrylate; the present invention can increase the curing crosslinking density by introducing a tetrafunctional monomer ethoxylated pentaerythritol tetraacrylate (PPTTA), thereby further increasing the strength of the blank.
[0024] Preferably, in the photocurable monomer, the mass ratio of o-phenylphenoxyethyl acrylate to ethoxylated pentaerythritol tetraacrylate is 1: (1.5-2.5), and further 1: 2. The present invention can simultaneously achieve a higher strength and curing depth of a single layer by controlling the mass ratio of o-phenylphenoxyethyl acrylate to ethoxylated pentaerythritol tetraacrylate within the above range. If the proportion of high refractive index (1.576) monomers is too high, the overcuring width is reduced, the precision is improved, but the strength of the single layer is reduced, which can easily lead to a decrease in interlayer bonding and delamination in multi-layer printing; if the proportion of high refractive index (1.576) monomers is too low, the curing depth is increased, the overcuring width is increased, the precision is reduced, and the internal stress is increased, which is prone to warping and deformation.
[0025] Preferably, in the photocurable monomer, the mass ratio of o-phenylphenoxyethyl acrylate to 1,6-hexanediol diacrylate is 1: (0.5-1.5), and further 1: 1. The present invention can achieve high solid content and high precision at the same time by controlling the mass ratio of o-phenylphenoxyethyl acrylate to 1,6-hexanediol diacrylate within the above range. If the proportion of HDDA monomer is too high, the overcuring width increases and the precision decreases; if the proportion of HDDA monomer is too low, on the one hand, it will lead to an increase in the viscosity of the slurry, making it difficult to obtain a ceramic slurry with a higher solid content, and on the other hand, it will lead to a decrease in the strength of the green body.
[0026] In this embodiment, in step S2, the mass ratio of the photocurable prepolymer to the photocurable monomer is 1:(3.5-4.5), and further 1:4.
[0027] In this embodiment, in step S2, the ball milling method is planetary ball milling under vacuum conditions, the ball milling time is 5 to 10 minutes, the rotation speed is 1000 to 2000 rpm, and the vacuum degree is -100 to -95 kPa. The present invention achieves uniform mixing of materials through vacuum ball milling and performs vacuum defoaming on the materials.
[0028] In this embodiment, in step S3, the volume proportion of the modified aluminum nitride powder in the photocurable ceramic slurry is 50% to 55%. The present invention can achieve uniform slurry spreading and obtain an aluminum nitride ceramic body with good printing quality and high density by controlling the volume proportion of the modified aluminum nitride powder within the above range.
[0029] In this embodiment, in step S3, the second wetting and dispersing agent is a polyphosphate wetting and dispersing agent, and the addition amount thereof is 2% to 4% of the mass of the modified aluminum nitride powder.
[0030] In some specific embodiments of the present invention, the second wetting and dispersing agent is BYK110.
[0031] In this embodiment, in step S3, the plasticizer is at least one of dioctyl phthalate (DOP) or dibutyl phthalate (DBP), and the added amount thereof is 4% to 10% of the mass of the photocurable ceramic slurry.
[0032] In this embodiment, in step S3, the photoinitiator is at least one of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO) and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide (TMO), and the added amount thereof is 0.5% to 1.5% of the mass of the photocuring premix.
[0033] In this embodiment, in step S3, the ball milling method is planetary ball milling under vacuum conditions, the ball milling time is 5 to 20 minutes, the rotation speed is 1500 to 2000 rpm, the vacuum degree is -100 to -95 kPa, the ball milling medium is zirconia balls with a diameter of 2 to 5 mm, and the mass ratio of zirconia balls to slurry is 1: (20 to 30). The present invention achieves uniform mixing of materials through vacuum ball milling and performs vacuum defoaming on the materials.
[0034] In this embodiment, in step S4, a surface exposure method is adopted, the wavelength is 405nm, and the exposure energy is 36-48mJ / cm 2 , the slice thickness is 20~30μm.
[0035] In this embodiment, in step S5, the cracking process includes: in a protective atmosphere, first heating to 250-350°C and keeping it for 1-3 hours, then heating to 500-600°C and keeping it for 1-3 hours, and the heating rate is 0.5-2°C / min. The present invention can ensure that various organic substances in the green body are fully cracked and avoid the generation of defects by adopting the above-mentioned staged insulation process.
[0036] In this embodiment, in step S5, the degreasing process includes: in air, the degreasing temperature is 500-600° C., the heat preservation time is 2-4 hours, and the heating rate is 0.5-2° C. / min.
[0037] In this embodiment, in step S5, the sintering process includes: pressureless sintering in a nitrogen atmosphere, a sintering temperature of 1600-1800° C., further 1680-1720° C., and a holding time of 1-10 hours, further 3-5 hours.
[0038] The present invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to actual conditions. In some specific embodiments of the present invention, the protective atmosphere is nitrogen or argon.
[0039] In a second aspect, the present invention provides a high thermal conductivity ceramic material, which is obtained by the additive manufacturing method of the high thermal conductivity ceramic material provided by the first aspect of the present invention.
[0040] Example 1 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0041] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0042] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry in which the volume proportion of modified aluminum nitride powder was 55 vol%.
[0043] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 85μm.
[0044] (5) The aluminum nitride ceramic body was placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then continued to heat to 550°C for 2 hours, cooled in the furnace and then heated to 600°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample was then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C for 3 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 219W / m·K.
[0045] Example 2 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0046] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0047] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.313 g of dibutyl phthalate (DBP), 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0048] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 48mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 96μm.
[0049] (5) The aluminum nitride ceramic body was placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then continued to heat to 550°C for 2 hours, cooled in the furnace and then heated to 600°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample was then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C for 3 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 220W / m·K.
[0050] Example 3 (1) Add 80g aluminum nitride powder (average particle size 1.2μm), 1.6g yttrium fluoride (average particle size 1.5μm), 4.0g samarium oxide (average particle size 2.0μm), 0.856g wetting dispersant BYK110 and 65g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0051] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1500 rpm, a mixing time of 5 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0052] (3) 8.177 g of photocuring premix, 0.8 g of wetting and dispersing agent BYK110, 3.509 g of dioctyl phthalate, 0.041 g of photoinitiator TMO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 1500 rpm, a mixing time of 20 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry in which the volume proportion of modified aluminum nitride powder was 50 vol%.
[0053] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 48mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 75μm.
[0054] (5) The aluminum nitride ceramic body was placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then continued to heat to 550°C for 2 hours, cooled in the furnace and then heated to 550°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample was then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1680°C for 5 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 206W / m·K.
[0055] Comparative Example 1 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0056] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0057] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0058] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 85μm.
[0059] (5) The aluminum nitride ceramic body was placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min for 1 hour in an air environment, then heated to 550°C for 2 hours, and then heated to 600°C at a rate of 0.5°C / min for 2 hours for degreasing. After degreasing, tiny cracks appeared on the surface and sides of the sample. This shows that the polymerized photosensitive resin in the body decomposed violently in a short period of time, causing defects such as cracking in the ceramic sample during the degreasing process.
[0060] Comparative Example 2 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0061] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0062] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0063] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 85μm.
[0064] (5) The aluminum nitride ceramic body is placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then heated to 550°C for 2 hours, and then heated to 600°C at a rate of 0.5°C / min for 2 hours. The degreasing body showed no cracks or delamination. The degreasing sample was pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C and a holding time of 3 hours. The density of the prepared aluminum nitride ceramic is only 2.57 g / cm 3 , much lower than 3.31 g / cm in Example 1 3 , indicating that the ceramic cannot be fully densified, and its thermal conductivity is only 46W / m·K. This is due to the high amount of organic matter in the 3D printed aluminum nitride blank, and the excessive carbon residue after thermal cracking hinders the sintering densification of the ceramic.
[0065] Comparative Example 3 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm) and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0066] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0067] (3) 6.656 g of photocuring premix, 1.8 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0068] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2, so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 137μm.
[0069] (5) The aluminum nitride ceramic body is placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then heated to 550°C for 2 hours, cooled in the furnace and heated to 600°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample is then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C for 3 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 194W / m·K. It can be seen that when the wetting dispersant is added to the photocuring ceramic slurry at one time, it affects the uniform dispersion of the sintering aid in the aluminum nitride powder, reduces the printing accuracy and the thermal conductivity of the ceramic.
[0070] Comparative Example 4 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0071] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0072] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0073] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2, so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and exposure printing is performed layer by layer to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 200μm.
[0074] (5) The aluminum nitride ceramic body is placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then heated to 550°C for 2 hours, cooled in the furnace and heated to 600°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample is then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C for 3 hours. The thermal conductivity of the prepared ceramic is 174W / m·K. Scanning electron microscopy revealed that there were tiny pores, cracks, etc. in some local areas of the sample ( Figure 4 ), indicating that the plasticizer not only helps to release the internal stress generated during photocuring and form microchannels during degreasing, thereby inhibiting the formation of pores and microcracks in the porcelain body after sintering, but also helps to reduce the over-curing width of 3D printing and improve the accuracy of the printed body.
[0075] Comparative Example 5 (1) Add 80g aluminum nitride powder (average particle size 1.2μm), 1.6g yttrium fluoride (average particle size 1.5μm), 4.0g samarium oxide (average particle size 2.0μm), 0.856g wetting dispersant BYK110 and 65g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0076] (2) The monofunctional monomer OPPEA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 2:2:1 at a rotation speed of 1500 rpm, a mixing time of 5 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0077] (3) 8.177 g of photocuring premix, 0.8 g of wetting and dispersing agent BYK110, 3.509 g of dioctyl phthalate, 0.041 g of photoinitiator TMO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 1500 rpm, a mixing time of 20 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0078] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2 , resulting in a single-layer curing depth of 50~55μm. The single-layer cured film is soft and has low strength. The cured layer is easily rolled up during the printing process, resulting in local missing parts of the blank and the inability to obtain a complete blank structure.
[0079] Comparative Example 6 (1) Add 80g aluminum nitride powder (average particle size 1.2μm), 1.6g yttrium fluoride (average particle size 1.5μm), 4.0g samarium oxide (average particle size 2.0μm), 0.856g wetting dispersant BYK110 and 65g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0080] (2) The difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 2:2:1 at a rotation speed of 1500 rpm, a mixing time of 5 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0081] (3) 8.177 g of photocuring premix, 0.8 g of wetting and dispersing agent BYK110, 3.509 g of dioctyl phthalate, 0.041 g of photoinitiator TMO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 1500 rpm, a mixing time of 20 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0082] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 48mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 170μm.
[0083] (5) The aluminum nitride ceramic body is placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then heated to 550°C for 2 hours, cooled in the furnace and heated to 550°C at a rate of 0.5°C / min under air for 2 hours for degreasing. The sample is then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1680°C for 5 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 200W / m·K. It can be seen that when there is no high refractive index monomer in the photosensitive resin, the accuracy of the printed body is significantly reduced.
[0084] Comparative Example 7 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0085] (2) According to the mass ratio of monofunctional monomer OPPEA, difunctional monomer HDDA, tetrafunctional monomer PPTTA and prepolymer epoxy acrylate (viscosity 30-60 Pa·s) of 1:1:2:1, the prepolymer epoxy acrylate was heated to 60°C and then added to the monomers and mixed in a planetary high-speed vacuum mixer at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0086] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0087] (4) The photocurable ceramic slurry is poured into the material tank of the 3D printer. Due to the high viscosity and poor fluidity of the slurry, it is difficult to spread it evenly on the printing table after being scraped by a scraper, and multi-layer printing cannot be performed.
[0088] Comparative Example 8 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0089] (2) The monofunctional monomer OPPEA, the difunctional monomer HDDA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 1:1:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0090] (3) 11.422 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.644 g of dioctyl phthalate, 0.114 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry in which the volume proportion of modified aluminum nitride powder was 45 vol%.
[0091] (4) Pour the photocurable ceramic slurry into the material tank of the 3D printer, use the surface exposure method, the wavelength is 405nm, and the exposure energy is set to 36mJ / cm 2 , so that the single-layer curing depth is 50~55μm. According to the three-dimensional model of the component, the slice thickness is set to 25μm, and layer-by-layer exposure printing is performed to obtain an aluminum nitride ceramic body, and its over-curing width is measured to be 82μm.
[0092] (5) The aluminum nitride ceramic body is placed in a degreasing furnace and heated to 300°C at a rate of 0.5°C / min under flowing nitrogen for 1 hour, then continued to heat to 550°C for 2 hours, cooled with the furnace, and then heated to 600°C at a rate of 0.5°C / min for 2 hours in an air environment for degreasing. The sample is then pressurelessly sintered in a nitrogen atmosphere at a sintering temperature of 1720°C for 3 hours. The thermal conductivity of the prepared aluminum nitride ceramic is 164W / m·K. It can be seen that when the solid content of the slurry is less than 50vol%, although a body with a printing accuracy of less than 100μm and tight interlayer bonding can be obtained, due to the low solid content, the density of the prepared ceramic decreases and the thermal conductivity is less than 200W / m·K.
[0093] Comparative Example 9 (1) Add 80g aluminum nitride powder (average particle size 1.68μm), 2.4g yttrium fluoride (average particle size 1.5μm), 1.6g samarium fluoride (average particle size 1.8μm), 0.42g wetting dispersant BYK110 and 60g anhydrous ethanol into a ball mill. The grinding balls are zirconium oxide balls with a diameter of 2-10mm and a total weight of 240g. Mill on a planetary ball mill for 6 hours at a speed of 365rpm. Pour out the slurry, dry it at 70℃, and pass it through a 100-mesh sieve to obtain modified aluminum nitride powder.
[0094] (2) The monofunctional monomer OPPEA, the tetrafunctional monomer PPTTA and the prepolymer difunctional aliphatic polyurethane acrylate (viscosity ~350 mPa·s) were mixed in a planetary high-speed vacuum mixer at a mass ratio of 2:2:1 at a rotation speed of 1000 rpm, a mixing time of 10 min, and a vacuum degree of -98 kPa to obtain a photocurable premix.
[0095] (3) 6.656 g of photocuring premix, 1.6 g of wetting and dispersing agent BYK110, 2.163 g of dioctyl phthalate, 0.065 g of photoinitiator TPO and 40 g of modified aluminum nitride powder were added to a light-shielded plastic jar in sequence, and zirconium oxide grinding balls with a diameter of 2-5 mm and a total weight of 2 g were added. The mixture was mixed in a planetary high-speed vacuum mixer at a speed of 2000 rpm, a mixing time of 15 min, and a vacuum degree of -98 kPa to obtain a photocuring ceramic slurry.
[0096] (4) The photocurable ceramic slurry is poured into the material tank of the 3D printer. Due to the high viscosity and poor fluidity of the slurry, it is difficult to spread it evenly on the printing table after being scraped by the scraper, and multi-layer printing cannot be performed.
[0097] See also Figure 1 ,pass Figure 1 It can be seen that the modified aluminum nitride powder prepared in Example 1 of the present invention has an ultraviolet absorbance of 0.1271 at 405 nm, indicating that the present invention significantly reduces the absorbance of the modified AlN powder by selecting a suitable sintering aid and a wetting and dispersing agent and coordinating the ball milling process.
[0098] See also Figure 2 ,pass Figure 2 It can be seen that the layers of the aluminum nitride ceramic body prepared in Example 1 of the present invention are tightly bonded to each other without defects such as delamination and pores.
[0099] See also Figure 3 ,pass Figure 3 It can be seen that the high thermal conductivity ceramic material prepared in Example 1 of the present invention has a complex shape, but after debinding and sintering, the shape is still complete and has no cracks.
[0100] See also Figure 4 ,pass Figure 4 It can be seen that after sintering, the aluminum nitride ceramic material prepared in Comparative Example 4 (without plasticizer) of the present invention has loose contact between grains in local areas and tiny cracks.
[0101] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for additive manufacturing of high thermal conductivity ceramic materials, characterized in that: The following steps are involved: Aluminum nitride, a sintering aid, a first wetting and dispersing agent, and an organic solvent are first ball-milled and mixed, and then dried and sieved to obtain modified aluminum nitride powder; The photocurable prepolymer and the photocurable monomer are mixed by a second ball milling process to obtain a photocurable premixed liquid; Under light-proof conditions, the modified aluminum nitride powder, the photocuring premix, the second wetting and dispersing agent, the plasticizer and the photoinitiator are mixed by a third ball milling process to obtain a photocuring ceramic slurry; According to the three-dimensional model of the component, the photocurable ceramic slurry is used to perform layer-by-layer printing and curing to obtain an aluminum nitride ceramic body; The aluminum nitride ceramic body is cracked, degreased and sintered in sequence to obtain a high thermal conductivity ceramic material.
2. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: The aluminum nitride is micron-sized aluminum nitride, and its average particle size is 1-2 μm; and / or, The sintering aid is a combination of at least one of samarium fluoride and samarium oxide and yttrium fluoride, the addition amount of which is 5% to 7% of the mass of the aluminum nitride, and the average particle size of which is 1 to 2 μm; and / or, The first wetting and dispersing agent is a phosphate wetting and dispersing agent, and the addition amount thereof is 0.5% to 1% of the total mass of the aluminum nitride and the sintering aid; and / or, The organic solvent is ethanol, and the amount of ethanol added is 70% to 80% of the total mass of the aluminum nitride and the sintering aid.
3. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: During the first ball milling mixing process, the ball milling method is planetary ball milling, the ball milling time is 5 to 10 hours, and the ball milling speed is 300 to 400 rpm; and / or, During the sieving process, the mesh size of the sieve is 100-200 meshes.
4. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: The photocurable prepolymer is a difunctional aliphatic polyurethane acrylate; and / or, The photocurable monomer is a combination of o-phenylphenoxyethyl acrylate, 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate; and / or, The mass ratio of the photocurable prepolymer to the photocurable monomer is 1:(3.5-4.5); and / or, During the second mixed ball milling process, the ball milling method is planetary ball milling under vacuum conditions, the ball milling time is 5 to 10 minutes, the rotation speed is 1000 to 2000 rpm, and the vacuum degree is -100 to -95 kPa.
5. The additive manufacturing method of high thermal conductivity ceramic material according to claim 4, characterized in that: In the photocurable monomer, the mass ratio of the o-phenylphenoxyethyl acrylate to the ethoxylated pentaerythritol tetraacrylate is 1:(1.5-2.5); and / or, The mass ratio of the o-phenylphenoxyethyl acrylate to the 1,6-hexanediol diacrylate is 1:(0.5-1.5).
6. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: In the photocurable ceramic slurry, the volume proportion of the modified aluminum nitride powder is 50% to 55%; and / or, The second wetting and dispersing agent is a polyphosphate wetting and dispersing agent, and the addition amount thereof is 2% to 4% of the mass of the modified aluminum nitride powder; and / or, The plasticizer is at least one of dioctyl phthalate and dibutyl phthalate, and the amount of the plasticizer added is 4% to 10% of the mass of the photocurable ceramic slurry; and / or, The photoinitiator is at least one of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide, and the amount of the photoinitiator added is 0.5% to 1.5% of the mass of the photocuring premix; and / or, During the third mixed ball milling process, the ball milling method is planetary ball milling under vacuum conditions, the ball milling time is 5 to 20 minutes, the rotation speed is 1500 to 2000 rpm, and the vacuum degree is -100 to -95 kPa.
7. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: The yttrium fluoride accounts for 25% to 60% of the total mass of the sintering aid; and / or, The first wetting and dispersing agent and the second wetting and dispersing agent are both BYK110.
8. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: During the printing and curing process, surface exposure was adopted with a wavelength of 405nm and an exposure energy of 36-48mJ / cm 2 , the slice thickness is 20~30μm.
9. The additive manufacturing method of high thermal conductivity ceramic material according to claim 1, characterized in that: The cracking process comprises: in a protective atmosphere, first heating to 250-350°C for 1-3 hours, then heating to 500-600°C for 1-3 hours, with a heating rate of 0.5-2°C / min; and / or, The degreasing process comprises: in air, the degreasing temperature is 500-600°C, the heat preservation time is 2-4 hours, and the heating rate is 0.5-2°C / min; and / or, The sintering process includes: pressureless sintering in a nitrogen atmosphere, a sintering temperature of 1600-1800° C., and a heat preservation time of 1-10 hours.
10. A high thermal conductivity ceramic material, characterized in that: The high thermal conductivity ceramic material is obtained by the additive manufacturing method of the high thermal conductivity ceramic material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high thermal conductivity and high strength aluminum nitride ceramics
CN108863393A
Aluminum nitride ceramic with high thermal conductivity and high strength and preparation method thereof
CN111484333A
Low-temperature sintered aluminum nitride ceramic material, aluminum nitride tape casting slurry and application
CN113200747A
Method for preparing high-performance aluminum nitride ceramic substrate through double doping of rare earth fluoride and scandium oxide
CN115010499A
Photocuring 3D printing slurry suitable for ceramic powder with high refractive index and high absorptivity and preparation method of photocuring 3D printing slurry
CN117466646A
Cited By
High-performance ceramic ultra-fast degreasing and sintering method based on photocuring additive manufacturing
CN121063941A